2023
DOI: 10.1051/0004-6361/202245300
|View full text |Cite
|
Sign up to set email alerts
|

New compact hierarchical triple system candidates identified using Gaia DR3

Abstract: Aims. We introduce a novel way to identify new compact hierarchical triple stars by exploiting the huge potential of Gaia DR3 and also its future data releases. We aim to increase the current number of compact hierarchical triple systems significantly. Methods. We used several eclipsing binary catalogs from different sky surveys that list a total of more than 1 million targets to search for Gaia DR3 non-single-star orbital solutions with periods substantially longer than the eclipsing periods of the binaries. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…This suggests that our previous hypothesis is reasonable. Recently, Czavalinga et al (2023) summarized the inner and outer periods of some discovered triple systems and found that most of the inner binary periods are less than 10 days, while most of the outer periods are larger than 300 days, which further confirms the validity of our hypothesis for most triple systems.…”
Section: The Dependence Of St Candidate Detection On Orbital Periodssupporting
confidence: 69%
See 2 more Smart Citations
“…This suggests that our previous hypothesis is reasonable. Recently, Czavalinga et al (2023) summarized the inner and outer periods of some discovered triple systems and found that most of the inner binary periods are less than 10 days, while most of the outer periods are larger than 300 days, which further confirms the validity of our hypothesis for most triple systems.…”
Section: The Dependence Of St Candidate Detection On Orbital Periodssupporting
confidence: 69%
“…Using the Hipparcos catalog, Eggleton and Tokovinin found that at least 10% of bright stars belong to triple-star (or multiple-star) systems (Eggleton & Tokovinin 2008. Czavalinga et al (2023) found 376 newly compact hierarchical triple (CHT) system candidates in their study. They considered that the orbital period is the most trustworthy orbital parameter and that other parameters should be used cautiously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 we present a set of four correlation plots among some of the physically interesting parameters associated with our collection of 33 recently analyzed triply eclipsing triples. To the seven sources presented in this work, we have added the 15 triples from our previous closely related papers (Rappaport et al 2022(Rappaport et al , 2023, as well as eleven triples studied in Borkovits et al (2019aBorkovits et al ( , 2020bBorkovits et al ( , 2022a, Czavalinga et al (2023b), andMitnyan et al (2020) using largely the same selection criteria and methods of analysis.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%